Gestational Trophoblastic Disorders: An Update in 2015 - Stevens, F. T.; Katzorke, N.; Tempfer, C.; Kreimer, U.; Bizjak, G. I.; Fleisch, M. C.; Fehm, T. N. (Geburtshilfe und Frauenheilkunde, 2015)
Gestational trophoblastic diseases (GTD) are a group of pregnancy-related disorders representing rare human tumours. They encompass premalignant disorders including complete (CHM), partial hydatidiform mole (PHM), exaggerated placental site (EPS), and placental-site nodule (PSN) as well as malignant disorders (also known as “gestational trophoblastic neoplasia [GTN]”) including invasive mole, choriocarcinoma (CC), placenta-site trophoblastic tumour (PSTT), and epitheloid trophoblastic tumours (ETT) (Fig. 1). Originally, GTD develop from abnormal proliferation of trophoblastic tissue and form botryoid arranged vesicles. Premalignant moles are usually treated by suction curettage while persistent and recurrent moles and malignant forms require systemic therapy with methotrexate or combination chemotherapy consisting of etoposide, actimomycin D, methotrexate, vincristine, and cyclophosphamide (EMA-CO). β-human chorion gonadotropin (β-hCG) plays a crucial role in diagnosis and monitoring therapeutic effects. Since the definitive diagnosis cannot be obtained by histology in most cases, persistent or recurrent disease is diagnosed by elevated or persistent serum levels of β-hCG. While curing rates are described to be as high as 98 %, GTD may initially present, recur, or end up as a metastasising systemic disease. This underlines the importance of a regular and consistent follow-up after treatment.
Keywords: gestational trophoblastic disease; hydatidiform moles; molar pregnancy; gestational neoplasia; human chorion gonadotropin